PEMODELAN ALOKASI KEUANGAN KOLEKTE MINGGU DALAM MENINGKATKAN KEKUATAN KEUANGAN PAROKI DI KEUSKUPAN AGUNG JAKARTA - Albertus Ary Dianto; Aries Heru Prasetyo (Jurnal Manajemen, 2021)
The Jakarta Archdiocese is a religious institution of the Catholic Church which as a religious institution has a specificity in managing its finances by referring to the Church Law and applicable public finance regulations. The characteristic of keuangan governance in the Jakarta Archdiocese can be seen from the implementation of the allocation and collection policies on Sundays, which are the main source of parish income. Funds obtained by parishes must be deposited to the diocese as a form of solidarity as stipulated in the percentage policy of the Pastoral Solidarity Fund, while the remaining funds in the parish are used to finance operations and other activities. The increasing number of parishes that apply for Collection II from year to year shows the increasing need for parish operational funds that must be met. Through the assessment of the DSP percentage policy, it is hoped that alternative keuangan modeling proposals will be obtained related to the policies implemented so that the parish has good keuangan strength. By conducting keuangan analysis based on keuangan position reports, activity reports and cash flow reports, we want to know the liquidity ratios that indicate the parish’s keuangan performance so that they can be taken into consideration in making appraisal assessments.